Pengaruh Pemberian Puding Pacinamum Terhadap Penurunan Kadar Glukosa Darah Penderita Diabetes Mellitus Tipe 2 Di Puskesmas Sukarami Palembang - Fatriani Fatriani; Terati Terati; Yulianto Yulianto; Ahmad Sadiq; Yunita Nazarena (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2021)
Background: Diabetes is a serious chronic disease that occurs because the pancreas does not produce enough insulin (a hormone that regulates blood sugar or glucose), or when the body cannot effectively use the insulin it produces. The purpose: of this study was to influence the administration of pacinamum pudding to the reduction in blood glucose levels in patients with type 2 diabetes mellitus at the 2020 voluntary puskesmas. Method: is quasi-experimental research with pre-test-post test design. Subjects of outpatient research without severe complications of type 2 Diabetes Mellitus in the Sukarami Health Center in Palembang City were taken by purposive sampling, the sample size in this study were 66 people who were randomly divided into 2 groups. The Results: of the study in the treatment group occurred when blood glucose levels decreased by 33.30 ± 28.39 mg / dl, whereas in the comparison group 21.66 ± 40.37 mg / dl. Statistical tests showed there were significant differences in the decrease in blood glucose levels during the treatment and comparison groups and there was no effect of pacinamum pudding on patients with type 2 diabetes. Conclusion: There was no effect of pacinamum pudding and oral hyperglycemic drugs (OHO) on blood glucose levels in Diabetes Mellitus patients with p-value <0.05 ie 0.257. Suggestion: Based on the results of this study, pacinamum pudding and oral hyperglycemic drugs (OHO) need to be considered and socialized to the wider community so that they can be used as a food source that is easy to find and has high efficacy to reduce blood glucose levels.